Transforming growth factor beta-1 and incidence of heart failure in older adults: the Cardiovascular Health Study. - Glazer, Nicole L; Macy, Elizabeth M; Lumley, Thomas; Smith, Nicholas L; Reiner, Alex P; Psaty, Bruce M; King, George L; Tracy, Russell P; Siscovick, David S (Cytokine, 2012)
CONTEXT: Transforming growth factor-beta1 (TGF-B1) is a highly pleiotropic cytokine whose functions include a central role in the induction of fibrosis. OBJECTIVE: To investigate the hypothesis that elevated plasma levels of TGF-B1 are positively associated with incident heart failure (HF). PARTICIPANTS AND METHODS: The hypotheses were tested using a two-phase case-control study design, ancillary to the Cardiovascular Health Study - a longitudinal, population-based cohort study. Cases were defined as having an incident HF event after their 1992-1993 exam and controls were free of HF at follow-up. TGF-B1 was measured using plasma collected in 1992-1993 and data from 89 cases and 128 controls were used for analysis. The association between TGF-B1 and risk of HF was evaluated using the weighted likelihood method, and odds ratios (OR) for risk of HF were calculated for TGF-B1 as a continuous linear variable and across quartiles of TGF-B1. RESULTS: The OR for HF was 1.88 (95% confidence intervals [CI] 1.26-2.81) for each nanogram increase in TGF-B1, and the OR for the highest quartile (compared to the lowest) of TGF-B1 was 5.79 (95% CI 1.65-20.34), after adjustment for age, sex, C-reactive protein, platelet count and digoxin use. Further adjustment with other covariates did not change the results. CONCLUSIONS: Higher levels of plasma TGF-B1 were associated with an increased risk of incident heart failure among older adults. However, further study is needed in larger samples to confirm these findings.
Keywords: Aged; Case-Control Studies; Health; Heart Failure; Humans; Incidence; Transforming Growth Factor beta1; United States

Associations between metabolic dysregulation and circulating biomarkers of fibrosis: the Cardiovascular Health Study. - Agarwal, Isha; Glazer, Nicole L; Barasch, Eddy; Djoussé, Luc; Gottdiener, John S; Ix, Joachim H; Kizer, Jorge R; Rimm, Eric B; Siscovick, David S; King, George L; Mukamal, Ken J (Metabolism, 2015)
AIM: Fibrosis is one postulated pathway by which diabetes produces cardiac and other systemic complications. Our aim was to determine which metabolic parameters are associated with circulating fibrosis-related biomarkers transforming growth factor-β (TGF-β) and procollagen type III N-terminal propeptide (PIIINP). METHODS: We used linear regression to determine the cross-sectional associations of diverse metabolic parameters, including fasting glucose, fasting insulin, body mass index, fatty acid binding protein 4, and non-esterified fatty acids, with circulating levels of TGF-β (n = 1559) and PIIINP (n = 3024) among community-living older adults in the Cardiovascular Health Study. RESULTS: Among the main metabolic parameters we examined, only fasting glucose was associated with TGF-β (P = 0.03). In contrast, multiple metabolic parameters were associated with PIIINP, including fasting insulin, body mass index, and non-esterified fatty acids (P<0.001, P<0.001, P=0.001, respectively). These associations remained statistically significant after mutual adjustment, except the association between BMI and PIIINP. CONCLUSIONS: Isolated hyperglycemia is associated with higher serum concentrations of TGF-β, while a broader phenotype of insulin resistance is associated with higher serum PIIINP. Whether simultaneous pharmacologic targeting of these two metabolic phenotypes can synergistically reduce the risk of cardiac and other manifestations of fibrosis remains to be determined.
Keywords: Aged; Aged, 80 and over; Biomarkers; Blood Glucose; Cardiovascular System; Cross-Sectional Studies; Diabetes Complications; Diabetes Mellitus; Fatty Acids, Nonesterified; Female; Fibrosis; Health; Humans; Insulin; Insulin Resistance; Male; Metabolic Diseases; Peptide Fragments; Procollagen; Transforming Growth Factor beta